RANCANGAN SISTEM INFORMASI PELANGGAN PADA KORAN HARIAN PAGI JAMBI STAR - Sri Mulyati (JURNAL AKADEMIKA)
This study aimed to determine the effect of the implementation of the Customer and Sales Fulfillment Harian Pagi Jambi Star newspaper. Customer Information Systems Harian Pagi Jambi Star newspaper built to facilitate processing of customer data that are arranged in a computerized newspaper. This information system consists of the input data ie customer data, shipment data, to process payments more efficiently with output more attractive and easier to understand, to be built using Visual Basic 6.0 Programming Language. The purpose of this study is to provide convenience during the processing of customer data, minimize errors in reporting, and improve the security of customer data to customer data security is guaranteed. Making it easier for the company to process customer data.